2007
DOI: 10.1007/s11062-007-0034-5
|View full text |Cite
|
Sign up to set email alerts
|

Key role of calcium signaling in synaptic transmission

Abstract: The review analyzes current concepts on the role of calcium signals in the process of synaptic neuron-toneuron and neuron-effector transmission and on the respective intracellular mechanisms (participation of different types of ion channels, mitochondria, and endoplasmic reticulum). The involvement of calcium both in the transmission per se, in particular in the process of exocytotic neurotransmitter release, and in longlasting modulations of the efficacy of synaptic transmission (potentiation or depression) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Several neurochemical mechanisms may account for the function of P2X4Rs in brain and behavioral functions, as well as its potential implication in neurodevelopmental and autism-related alterations. P2X4Rs have substantial calcium permeability (Egan and Khakh, 2004;North, 2002;Soto et al, 1996); thus, the lack of P2X4Rs is likely to result to alterations of calcium homeostasis, which may in turn lead to alterations in synaptic transmission and higher vulnerability to abnormalities of neural plasticity (Kostyuk, 2007). P2X4Rs have been shown to exert complex modulatory effects on the function and/or composition of other receptors, including NMDA (Baxter et al, 2011) and AMPA (Andries et al, 2007) receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Several neurochemical mechanisms may account for the function of P2X4Rs in brain and behavioral functions, as well as its potential implication in neurodevelopmental and autism-related alterations. P2X4Rs have substantial calcium permeability (Egan and Khakh, 2004;North, 2002;Soto et al, 1996); thus, the lack of P2X4Rs is likely to result to alterations of calcium homeostasis, which may in turn lead to alterations in synaptic transmission and higher vulnerability to abnormalities of neural plasticity (Kostyuk, 2007). P2X4Rs have been shown to exert complex modulatory effects on the function and/or composition of other receptors, including NMDA (Baxter et al, 2011) and AMPA (Andries et al, 2007) receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Analogous currents were observed in acutely isolated neurons of the spinal dorsal horn. It was demonstrated that not only Ca 2+ ions but also other ions can pass through the corresponding channels, and this induces the pain syndrome [25,26]. As was noted, application of capsaicin to differentiated afferent units causes modulation of voltage-dependent calcium currents just in small-sized DRG neurons [21].…”
Section: Role Of Transmembrane Calcium Currents In Transmission Of Nomentioning
confidence: 89%
“…To elucidate the direct role of Ca 2+ in intracellular processes related to generation of nociceptive signals and their transmission within the CNS, a number of studies of transmembrane calcium currents in primary afferent and central relay neurons of the nociceptive system were carried out [25].…”
Section: Role Of Transmembrane Calcium Currents In Transmission Of Nomentioning
confidence: 99%
“…ITSN1 is an important player in synaptic vesicle cycling [6]. It is widely accepted that the majority of molecular events associated with the synaptic vesicle trafficking are triggered by changes in Ca 2+ concentration and subsequent activation of the Ca 2+ -dependent proteins, particularly kinases and phosphatases [7]. In this work we tested the hypothesis that ITSN1 may undergo the Ca 2+ /calmodulin-dependent phosphorylation.…”
mentioning
confidence: 97%